2000
DOI: 10.1046/j.1365-2516.2000.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive choices of women in families with haemophilia

Abstract: To assess women's experiences in pregnancy and attitudes towards their reproductive choices, a structured questionnaire was sent to all obligate and potential carriers of haemophilia (A and B), aged 14-60 years, registered with our haemophilia centre. One hundred and ninety-seven of 545 (36%) returned completed questionnaires. Clinical details, including type and severity of the disease in the family and results of DNA analysis for carrier detection, were obtained from patient notes. One hundred and sixty wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 6 publications
0
55
0
Order By: Relevance
“…10 Reported maternal mortality by the Central Bureau of Statistics during pregnancy and delivery, however, is so low, at 3-6 per l million women in 1995, that a noticeable effect on our results is extremely unlikely. Finally, the presence of a severe hereditary disease in the family could promote health-conscious behaviour within the family.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…10 Reported maternal mortality by the Central Bureau of Statistics during pregnancy and delivery, however, is so low, at 3-6 per l million women in 1995, that a noticeable effect on our results is extremely unlikely. Finally, the presence of a severe hereditary disease in the family could promote health-conscious behaviour within the family.…”
Section: Discussionmentioning
confidence: 55%
“…Because they have one unaffected allele, carriers have concentrations of clotting factor VIII or IX of about 50% of normal and, hence, decreased coagulability.'' 10 However, if carriers do have an increased bleeding tendency, it is mild. 11 To determine whether a mild, in most cases asymptomatic, decreased coagulability protects against ischaemic cardiovascular events, we compared overall and cause-specific mortality in carriers of the recessive gene for haemophilia with that in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,24 Consequently, many pregnant women from at-risk families do not consent to invasive testing because of the associated risks. 25,26 Noninvasive fetal sex determination by the use of circulating fetal DNA has provided one safe alternative for managing such pregnancies. 27 Through the detection of chromosome Y DNA sequences in maternal plasma, male fetuses could be identified with an accuracy of greater than 97% from the 7th week of gestation onwards.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3%-4% of infants with hemophilia experience a cranial bleed 30 that occurs during labor and delivery. Prolonged labor and difficult instrumental deliveries are the main risk factors for this complication 25,26 and should be avoided for delivery of affected fetuses. 18 It is also recommended that affected fetuses are delivered in a tertiary unit with an affiliated hemophilia center to ensure availability of necessary expertise and resources for their management.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-four percent of women reported that having haemophilia was a major factor in this decision; 44% of women did not want to transfer haemophilia to their child, 6% had previous experience of haemophilia in the family, and 27% reported personal, social, financial and medical reasons for this decision. 15 This questionnaire survey revealed individuals' priorities in different life situations, such as the prime example of disease influence on having children. Various studies suggest that the decision to have genetic testing could be a life changing decision and may impact on family planning, interpersonal relationships, social, financial and employment aspects.…”
Section: Having Childrenmentioning
confidence: 99%